Condom equals developmentn ; Pitfall ; Weaver of songs [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Tackles government program on birth and population control; Marcopper's mine tailings disposal into Calancan Bay in Marinduque; and an interview with Susan about her songs on the realities of poverty and exploitation.
Contents : Condom equals developmentn (16 min.) -- Pitfall (19 min.) -- Weavers of songs (17 min.)
Keywords: Birth control -- Government policy -- Philippines; Family planning -- Philippines; Pollution -- Philippine mental aspects; Protest songs -- Philippines; Waste disposal sites -- Philippines